Visceral parasites in wildfowl - Soulsby, E J L (Wildfowl, 1957)
During the 1956-57 season 46 viscera were examined in order to ascertain the type and degree of parasitism which occurs under natural conditions. Ten species of wildfowl were represented in the samples, the distribution being as follows: Shoveler 3, Mallard 3, Teal 15, Wigeon 12, Grelag Goose 1, Velvet Scoter 3, Common Scoter 4, Goldeneye 1, Shelduck 3, Tufted Duck 1. Parasites found-Nematodes (Roundworms): Amidostomum anseris, Tetrameres fissipina, Echinuria horrida.